The Dynamics of Halal Lifestyle Among Pesantren Students in Food and Beverage Consumption - Siti Rodiah Rodiah; Muhammad Noor Harisuddin; Abdul Rokhim (The Eastasouth Management and Business, 2026)
The halal lifestyle has emerged as an increasingly prominent topic within the global discourse on Muslim consumer behavior. In the context of Islamic boarding schools (pesantren), the halal lifestyle practiced by students is not only understood as adherence to jurisprudential rules but also represents religious identity and the integration of spiritual values into daily practices. This review examines the dynamics of the halal lifestyle among pesantren students, particularly in their consumption of food and beverages, through an extensive analysis of academic literature. Relevant international and national studies on halal lifestyle, pesantren education, religious consumption behavior, and the evolution of halal culture were critically reviewed. Findings indicate that the development of halal lifestyle among pesantren students is shaped by religious literacy, institutional policies, availability of halal products, socio-economic changes, and digital transformation. The halal lifestyle of pesantren students is dynamic, adaptive, and continuously evolving in response to shifts in information ecosystems and social practices. Strengthening halal literacy within pesantren institutions is crucial to ensure consistent understanding and application of the principles of halalan thayyiban.